Accuracy of musculoskeletal imaging for the diagnosis of polymyalgia rheumatica: systematic review. Issue 1 (13th August 2015) - Mackie, Sarah Louise; Koduri, Gouri; Hill, Catherine L; Wakefield, Richard J; Hutchings, Andrew; Loy, Clement; Dasgupta, Bhaskar; Wyatt, Jeremy C
Abstract : Objectives: To review the evidence for accuracy of imaging for diagnosis of polymyalgia rheumatica (PMR). Methods: Searches included MEDLINE, EMBASE and PubMed. Evaluations of diagnostic accuracy of imaging tests for PMR were eligible, excluding reports with <10 PMR cases. Two authors independently extracted study data and three authors assessed methodological quality using modified QUADAS-2 criteria. Results: 26 studies of 2370 patients were evaluated: 10 ultrasound scanning studies; 6 MRI studies; 1 USS and MRI study; 7 18-fluorodeoxyglucose-positron emission tomography (PET) studies; 1 plain radiography and 1 technetium scintigraphy study. In four ultrasound studies, subacromial-subdeltoid bursitis had sensitivity 80% (95% CI 55% to 93%) and specificity 68% (95% CI 60% to 75%), whereas bilateral subacromial-subdeltoid bursitis had sensitivity 66% (95% CI 43% to 87%) and specificity 89% (95% CI 66% to 97%). Sensitivity for ultrasound detection of trochanteric bursitis ranged from 21% to 100%. In four ultrasound studies reporting both subacromial-subdeltoid bursitis and glenohumeral synovitis, detection of subacromial-subdeltoid bursitis was more accurate than that of glenohumeral synovitis (p=0.004). MRI and PET/CT revealed additional areas of inflammation in the spine and pelvis, including focal areas between the vertebrae and anterior to the hip joint, but the number of controls with inflammatory disease was inadequate for precise specificity estimates. Conclusions: Subacromial-subdeltoid bursitis appears to be the most helpful ultrasound feature for PMR diagnosis, but interpretation is limited by study heterogeneity and methodological issues, including variability in blinding and potential bias due to case–control study designs. Recent MRI and PET/CT case–control studies, with blinded readers, yielded promising data requiring validation within a diagnostic cohort study.